Is there an epilepsy belt of high prevalence rate in China? - Wu, Li; Ye, Zeming; Li, Youfu; Luo, Ming; Li, Shaojun; Mi, Hongyan; Qiu, Zhihua; Jiang, Yongjun (Frontiers in Neurology, 2022)
Background Epilepsy is one of the leading neurological diseases. Our study is aimed to determine whether there is a focal region of high epilepsy prevalence in China. Methods All studies published between 1981 and 2020 investigating the prevalence of epilepsy in China were systematically reviewed. The geographical location, sample size, number of cases, urbanization rate, gross domestic product (GDP) per capita, percentage of less than 15 years old, and medical insurance per capita were derived and analyzed. Criteria for a provincial region of high prevalence was defined as with higher epilepsy prevalence than the average prevalence of epilepsy in China. Results A total of 60 studies provided data on the prevalence of epilepsy in 29 of 33 provincial regions of China. The average prevalence in China was 1.68‰, and 12 provincial regions met our criteria for a region of high epilepsy prevalence and constitute an epilepsy belt ranging along the division between the second step and the third step of China. The prevalence in the epilepsy belt was 331.9 per 100000 population compared with 125.3 in regions outside the belt (P<0.05). Surprisingly, there was no significant difference in sample size, number of cases, urbanization rate, GDP per capita, percentage of less than 15 years old, or medical insurance per capita between the regions in and outside the epilepsy belt. Conclusions An epilepsy belt of high prevalence exists in 12 provincial regions locating along the division between the second step and the third step of China.